Relaciones entre ficción y mediatización: examen de seis momentos - Proyecto - Traversa, Oscar (2015)
The purpose of the current project is to determine the kind of relationships which link Fiction (as a textual product) with the phenomenon of Mediatization. The relationships between these two entities had been summoned up in occidental culture since antiquity; although those bonds were formulated through different notions, always in a partial and various ways, and always associated with the typical modality of thought of their own time. The intent of this examination is to go critically through these modalities in order to give them an order and a reformulation, using the contemporary resources specific to Semiotics and those to Scientific Historiography. The investigation will be restricted to the last 200 years -when the Mediatization started to accelerate dramatically-, including some moments which are susceptible to establish chains and connections that could be associated to other historical moments.